2021
DOI: 10.1016/j.parkreldis.2021.07.014
|View full text |Cite
|
Sign up to set email alerts
|

C19orf12 mutation causing mitochondrial membrane-protein Associated Neurodegeneration masquerading as spastic paraplegia

Abstract: Mitochondrial Membrane-protein Associated Neurodegeneration (MPAN) is a rare disease, caused by C19orf12 mutations and up to 29 different mutations have been described. We report a young woman presented with spastic paraparesis due to C19orf12 gene. MPAN presenting like Hereditary spastic paraplegia-43 is rare and the genetic mutation had been described only once in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Most described cases are either rare manifestations of a common disorder, or a common manifestation of a rare disorder. In this issue of PRD, the case reported by Deenadayalu & Ramesh et al, [13] is a good example of a rare manifestation of a rare genetic disorder-a potential trap for clinicians and geneticists alike. The authors reported a case of mitochondrial membrane protein-associated neurodegeneration (MPAN) with an early onset and slowly progressive spastic paraparesis, plus mild ataxia, optic atrophy, and cognitive compromise.…”
Section: Neurodegeneration With Brain Iron Accumulation Nbia Mitochondrial Membrane Protein-associated Neurodegeneration Mpan Spastic Parmentioning
confidence: 99%
“…Most described cases are either rare manifestations of a common disorder, or a common manifestation of a rare disorder. In this issue of PRD, the case reported by Deenadayalu & Ramesh et al, [13] is a good example of a rare manifestation of a rare genetic disorder-a potential trap for clinicians and geneticists alike. The authors reported a case of mitochondrial membrane protein-associated neurodegeneration (MPAN) with an early onset and slowly progressive spastic paraparesis, plus mild ataxia, optic atrophy, and cognitive compromise.…”
Section: Neurodegeneration With Brain Iron Accumulation Nbia Mitochondrial Membrane Protein-associated Neurodegeneration Mpan Spastic Parmentioning
confidence: 99%